Fluorine-containing copolymer
Patent Information
- Application Number
- JP2023074965
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2023-04-28
- Publication Date
- 2025-01-30
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing fluorine-containing copolymers fail to provide molded articles with excellent toughness, solvent crack resistance, low hydrogen permeability, rigidity at high temperatures, tensile creep resistance, and durability against repeated loads, particularly when used in applications involving high-temperature and high-pressure chemical environments.
A fluorine-containing copolymer comprising tetrafluoroethylene, hexafluoropropylene, and perfluoro(propyl vinyl ether units, with specific content ratios and melt flow rates, allowing for improved wear resistance, solvent crack resistance, low hydrogen permeability, rigidity at high temperatures, and durability against repeated loads.
The copolymer enables the production of molded articles with enhanced properties, including beautiful injection-molded bodies and thin films with uniform thickness at high molding speeds, suitable for applications requiring high temperature resistance and durability.
Abstract
Description
[Technical Field]
[0001] The present disclosure relates to a fluorine-containing copolymer. [Background technology]
[0002] Patent Document 1 describes a partially crystalline copolymer comprising tetrafluoroethylene, hexafluoropropylene in an amount equivalent to 2.8 to about 5.3 HFPI, and 0.2 to 3% by weight of perfluoro(ethyl vinyl ether). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-52920 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present disclosure is to provide a fluorocopolymer which can be molded by injection molding to give beautiful injection-molded articles, or can be molded by extrusion molding to give thin films of uniform thickness at a high molding speed, and which can give molded articles which have excellent abrasion resistance at 65°C, solvent crack resistance, low hydrogen permeability, rigidity at a high temperature of 75°C, tensile creep resistance at 130°C, and durability against repeated loads. [Means for solving the problem]
[0005] According to the present disclosure, there is provided a fluorine-containing copolymer containing tetrafluoroethylene units, hexafluoropropylene units and perfluoro(propyl vinyl ether) units, wherein the content of hexafluoropropylene units is 9.4 to 10.3 mass% based on all monomer units, the content of perfluoro(propyl vinyl ether) units is 0.8 to 1.6 mass% based on all monomer units, and the melt flow rate at 372°C is 7.0 to 17.0 g / 10 min.
[0006] The content of hexafluoropropylene units is preferably 9.6 to 10.2% by mass based on the total monomer units. The content of perfluoro(propyl vinyl ether) units is preferably 0.8 to 1.4% by mass based on the total monomer units. The melt flow rate at 372°C is preferably 7.5 to 15.0 g / 10 min. The number of -CF2H is 10 6 It is preferable that the fluorine-containing copolymer is one according to any one of claims 1 to 4, in which the number of the fluorine-containing copolymers per unit area is 50 or more. The total number of carbonyl-containing end groups, -CF=CF2 and -CH2OH, is 10 main chain carbon atoms. 6 It is preferable that the number of particles per particle is 90 or less.
[0007] The present disclosure also provides an injection-molded article containing the above-mentioned fluorocopolymer.
[0008] The present disclosure also provides a coated electric wire having a coating layer containing the above-mentioned fluorine-containing copolymer.
[0009] The present disclosure also provides a molded article containing the above-mentioned fluorocopolymer, which is a housing for storing a filter or an adsorbent, a piping member, a tube, a film, or an electric wire coating. [Effects of the Invention]
[0010] According to the present disclosure, it is possible to provide a fluorocopolymer which can be molded by injection molding to give a beautiful injection-molded article, or can be molded by extrusion molding to give a thin film of uniform thickness at a high molding speed, and which can give a molded article which has excellent abrasion resistance at 65°C, solvent crack resistance, low hydrogen permeability, rigidity at a high temperature of 75°C, tensile creep resistance at 130°C, and durability against repeated load. DETAILED DESCRIPTION OF THE INVENTION
[0011] Specific embodiments of the present disclosure will be described in detail below, but the present disclosure is not limited to the following embodiments.
[0012] The fluorine-containing copolymer of the present disclosure contains tetrafluoroethylene (TFE) units, hexafluoropropylene (HFP) units and perfluoro(propyl vinyl ether) (PPVE) units.
[0013] Patent Document 1 proposes a TFE / HFP / PEVE copolymer that is endowed with a high extrusion rate and high stress crack resistance by using perfluoro(ethyl vinyl ether) (PEVE) instead of PPVE as a melt-processable tetrafluoroethylene copolymer.
[0014] Filters or adsorbents used in the production or use of chemicals are sometimes used to treat high-temperature chemical solutions. Housings for such filters or adsorbents are required to have rigidity that prevents expansion even when in contact with high-temperature, high-pressure chemical solutions, tensile creep resistance, and durability against repeated loads. However, conventional copolymers have a problem in that they cannot be used to obtain molded articles that are excellent in rigidity, particularly at high temperatures.
[0015] It has been found that by adjusting the contents of HFP units and PPVE units in a fluorocopolymer containing TFE units, HFP units and PPVE units, and the melt flow rate within very limited ranges, the abrasion resistance at 65°C, solvent crack resistance, low hydrogen permeability, rigidity at a high temperature of 75°C, tensile creep resistance at 130°C and durability against repeated load of a molded article obtained from the fluorocopolymer can be significantly improved. Furthermore, the fluorocopolymer of the present disclosure can be molded by injection molding to give a beautiful injection-molded article.
[0016] Moreover, by molding the fluorocopolymer of the present disclosure by extrusion molding, it is possible to form a very thick coating layer of uniform thickness on a core wire having a very large diameter, thereby obtaining an attractive tube, and furthermore, it is possible to mold it into a thin film of uniform thickness at a high molding speed. Thus, the fluorocopolymer of the present disclosure can be used not only as a material for a housing for storing a filter or an adsorbent, or for piping components, but also in a wide range of applications such as tubes, films, or electric wire coatings.
[0017] The fluorocopolymers of the present disclosure are melt-processable fluororesins, which means that the polymers can be melted and processed using conventional processing equipment such as extruders and injection molding machines.
[0018] The content of HFP units in the fluorine-containing copolymer is 9.4 to 10.3% by mass, preferably 9.5% by mass or more, more preferably 9.6% by mass or more, and preferably 10.2% by mass or less, based on the total monomer units. If the content of HFP units is too low, it is impossible to obtain a molded product having excellent abrasion resistance at 65°C and solvent crack resistance. If the content of HFP units is too high, it is impossible to obtain a molded product having excellent rigidity at a high temperature of 75°C, tensile creep resistance at 130°C, and durability against repeated loads.
[0019] The content of PPVE units in the fluorine-containing copolymer is 0.8 to 1.6% by mass, preferably 1.5% by mass or less, more preferably 1.4% by mass or less, even more preferably 1.3% by mass or less, particularly preferably 1.2% by mass or less, and most preferably 1.1% by mass or less, based on the total monomer units. If the content of PPVE units is too low, a molded product having excellent abrasion resistance at 65°C and solvent crack resistance cannot be obtained. If the content of PPVE units is too high, a molded product having excellent rigidity at high temperatures of 75°C cannot be obtained.
[0020] The content of TFE units in the fluorine-containing copolymer is preferably 88.1% by mass or more, more preferably 88.2% by mass or more, even more preferably 88.4% by mass or more, and preferably 89.8% by mass or less, more preferably 89.7% by mass or less, and even more preferably 89.6% by mass or less, based on the total content of all monomer units. The content of TFE units may be selected so that the total content of HFP units, PPVE units, TFE units and other monomer units is 100% by mass.
[0021] The fluorine-containing copolymer of the present disclosure may be a copolymer containing only the above three monomer units, or a copolymer containing the above three monomer units and other monomer units, so long as it contains the above three monomer units.
[0022] The other monomer is not particularly limited as long as it is a monomer copolymerizable with TFE, HFP, and PPVE, and may be a fluoromonomer or a non-fluorine-containing monomer.
[0023] Fluoromonomers include chlorotrifluoroethylene, vinyl fluoride, vinylidene fluoride, trifluoroethylene, hexafluoroisobutylene, CH2=CZ 1 (CF2) n Z 2 (In the formula, Z 1 is H, F, Z 2 is H, F or Cl, and n is an integer of 1 to 10),1 (In the formula, Rf 1 Perfluoro(alkyl vinyl ether) [PAVE] (excluding PPVE) represented by CF2=CF-O-CH2-Rf 2 (In the formula, Rf 2 is preferably at least one selected from the group consisting of alkyl perfluorovinyl ether derivatives represented by a perfluoroalkyl group having 1 to 5 carbon atoms, perfluoro-2,2-dimethyl-1,3-dioxole [PDD], and perfluoro-2-methylene-4-methyl-1,3-dioxolane [PMD].
[0024] CH2=CZ 1 (CF2) n Z 2 Examples of the monomer represented by the formula include CH2=CFCF3, CH2=CH-C4F9, and CH2=CH-CF 13 , CH2=CF-C3F6H, etc.
[0025] CF2=CF-ORf 1 Examples of the perfluoro(alkyl vinyl ether) represented by the formula include CF2=CF-OCF3, CF2=CF-OCF2CF3, and the like.
[0026] Examples of the fluorine-free monomer include hydrocarbon-based monomers copolymerizable with TFE, HFP, and PPVE. Examples of the hydrocarbon-based monomer include alkenes such as ethylene, propylene, butylene, and isobutylene; alkyl vinyl ethers such as ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, isobutyl vinyl ether, and cyclohexyl vinyl ether; vinyl acetate, vinyl propionate, vinyl n-butyrate, vinyl isobutyrate, vinyl valerate, vinyl pivalate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl versatate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl benzoate, vinyl p-t-butylbenzoate, vinyl cyclohexanecarboxylate, vinyl monochloroacetate, and vinyl adipate. vinyl esters such as vinyl allyl ether, vinyl acrylate, vinyl methacrylate, vinyl crotonate, vinyl sorbate, vinyl cinnamate, vinyl undecylenate, vinyl hydroxyacetate, vinyl hydroxypropionate, vinyl hydroxybutyrate, vinyl hydroxyvalerate, vinyl hydroxyisobutyrate, and vinyl hydroxycyclohexanecarboxylate; alkyl allyl ethers such as ethyl allyl ether, propyl allyl ether, butyl allyl ether, isobutyl allyl ether, and cyclohexyl allyl ether; and alkyl allyl esters such as ethyl allyl ester, propyl allyl ester, butyl allyl ester, isobutyl allyl ester, and cyclohexyl allyl ester.
[0027] The fluorine-free monomer may also be a functional group-containing hydrocarbon monomer copolymerizable with TFE, HFP, and PPVE. Examples of the functional group-containing hydrocarbon monomer include hydroxyalkyl vinyl ethers such as hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, hydroxyisobutyl vinyl ether, and hydroxycyclohexyl vinyl ether; fluorine-free monomers having a glycidyl group such as glycidyl vinyl ether and glycidyl allyl ether; fluorine-free monomers having an amino group such as aminoalkyl vinyl ether and aminoalkyl allyl ether; fluorine-free monomers having an amide group such as (meth)acrylamide and methylol acrylamide; bromine-containing olefins, iodine-containing olefins, bromine-containing vinyl ethers, iodine-containing vinyl ethers; and fluorine-free monomers having a nitrile group.
[0028] The content of other monomer units in the fluorine-containing copolymer of the present disclosure is preferably 0 to 1.7% by mass, more preferably 1.0% by mass or less, still more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less, based on the total amount of monomer units.
[0029] The melt flow rate (MFR) of the fluorine-containing copolymer is 7.0 to 17.0 g / 10 min, preferably 7.1 g / 10 min or more, more preferably 7.2 g / 10 min or more, even more preferably 7.3 g / 10 min or more, still more preferably 7.4 g / 10 min or more, particularly preferably 7.5 g / 10 min or more, most preferably 8.8 g / 10 min or more, preferably 16.9 g / 10 min or less, more preferably 16.5 g / 10 min or less, even more preferably 16.0 g / 10 min or less, still more preferably 15.0 g / 10 min or less, especially preferably 12.8 g / 10 min or less, particularly preferably 11.0 g / 10 min or less, and most preferably 10.0 g / 10 min or less. If the MFR is too low, a molded product with excellent low hydrogen permeability cannot be obtained. If the MFR is too low, it is impossible to obtain a beautiful injection-molded article by injection molding, and it is impossible to extrude a thin film of uniform thickness at a high molding speed by extrusion molding.If the MFR is too high, it is impossible to obtain a molded article having excellent abrasion resistance at 65°C and solvent crack resistance.
[0030] In the present disclosure, the melt flow rate is a value obtained in accordance with ASTM D-1238 using a Melt Indexer G-01 (manufactured by Toyo Seiki Seisakusho, Ltd.) as the mass (g / 10 min) of polymer flowing out of a die having an inner diameter of 2 mm and a length of 8 mm at 372°C under a load of 5 kg per 10 min.
[0031] The MFR can be adjusted by adjusting the type and amount of a polymerization initiator used when polymerizing the monomers, the type and amount of a chain transfer agent, and the like.
[0032] The fluorocopolymer of the present disclosure may or may not have -CF2H. It is preferable that the fluorocopolymer of the present disclosure has -CF2H, since this makes it less likely that molding defects such as foaming will occur when the fluorocopolymer is melt-molded, and the fluorocopolymer will have excellent heat resistance. The number of -CF2H in the fluorocopolymer is preferably 10 or more, and more preferably 10 or more. 6The number per unit is preferably 50 or more, more preferably 60 or more, even more preferably more than 90, still more preferably more than 120, still more preferably more than 150, particularly preferably 200 or more, and most preferably 300 or more. There is no particular upper limit to the number of -CF2H groups, and it may be, for example, 800. The number of -CF2H groups can be adjusted, for example, by appropriately selecting the type of polymerization initiator or chain transfer agent, or by wet heat treatment or fluorination treatment of the fluorinated copolymer described below.
[0033] The fluorine-containing copolymer of the present disclosure may or may not have -COF, -COOH, or -CH2OH. The fluorine-containing copolymer of the present disclosure is a copolymer in which the total number of -COF, -COOH, and -CH2OH is 10 or less. 6 It is preferably 90 or less per unit. The total number of -COF, -COOH and -CH2OH groups is, in order of preference, 80 or less, 70 or less, 60 or less and 50 or less. When the total number of -COF, -COOH and -CH2OH groups is within the above range, molding defects such as foaming are less likely to occur when the fluorocopolymer is melt-molded, and the fluorocopolymer has excellent heat resistance. The total number of -COF, -COOH and -CH2OH groups can be adjusted, for example, by appropriately selecting the type of polymerization initiator or chain transfer agent, or by subjecting the fluorocopolymer to a wet heat treatment or fluorination treatment described below.
[0034] The fluorine-containing copolymer of the present disclosure may or may not have a carbonyl group-containing end group, -CF=CF2 or -CH2OH. The fluorine-containing copolymer of the present disclosure has a main chain carbon number of 10 or more, and the total number of the carbonyl group-containing end groups, -CF=CF2 and -CH2OH is 10 or less. 6It is preferably 90 or less per unit area. The total number of carbonyl group-containing end groups, -CF=CF2 and -CH2OH is, in order of preference, 80 or less, 70 or less, 60 or less and 50 or less. When the total number of carbonyl group-containing end groups, -CF=CF2 and -CH2OH is within the above range, molding defects such as foaming are less likely to occur when the fluorocopolymer is melt-molded, and the fluorocopolymer has excellent heat resistance. The total number of carbonyl group-containing end groups, -CF=CF2 and -CH2OH can be adjusted, for example, by appropriately selecting the type of polymerization initiator or chain transfer agent, or by subjecting the fluorocopolymer to a wet heat treatment or fluorination treatment, as described below.
[0035] Examples of the carbonyl group-containing terminal group include -COF, -COOH, -COOR (R is an alkyl group), -CONH2, and -O(C=O)OR (R is an alkyl group). The type of alkyl group (R) in -COOR and -O(C=O)OR is determined by the polymerization initiator, chain transfer agent, etc. used in producing the fluorine-containing copolymer, and is, for example, an alkyl group having 1 to 6 carbon atoms, such as -CH3.
[0036] The fluorine-containing copolymer of the present disclosure may or may not have -O(C=O)OR (R is an alkyl group). The fluorine-containing copolymer of the present disclosure has a main chain carbon number of 10 or more, and the total number of -O(C=O)OR (R is an alkyl group) is 10 or more. 6 It is preferably 90 or less per unit area. The total number of -O(C=O)OR (R is an alkyl group) is, in order of preference, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, and 15 or less, and may be below the limit of quantitation (ND). The total number of -O(C=O)OR (R is an alkyl group) can be adjusted, for example, by appropriately selecting the type of polymerization initiator or chain transfer agent, or by subjecting the fluorinated copolymer to a wet heat treatment or fluorination treatment described below.
[0037] Infrared spectroscopy can be used to identify the type of functional group and measure the number of functional groups.
[0038] The number of functional groups is specifically measured by the following method. First, the fluorocopolymer is molded by cold pressing to prepare a film having a thickness of 0.25 to 0.30 mm. This film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the fluorocopolymer, and a difference spectrum is obtained from a base spectrum in which the copolymer is completely fluorinated and no functional groups are present. From the absorption peaks of specific functional groups appearing in this difference spectrum, the number of carbon atoms in the fluorocopolymer is determined according to the following formula (A): 6 Calculate the number of functional groups per molecule, N.
[0039] N=I×K / t (A) I: Absorbance K: Correction coefficient t: film thickness (mm)
[0040] For reference, the absorption frequencies, molar absorption coefficients, and correction factors for several functional groups are shown in Table 1. The molar absorption coefficients were determined from FT-IR measurement data of low-molecular-weight model compounds. [Table 1]
[0041] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are shown in the table, and are several tens of Kaiser (cm) from the absorption frequencies of -CF2H, -COF, -COOH free and -COOH bonded, -COOCH3, and -CONH2, respectively. -1 ) becomes lower.
[0042] For example, the number of functional groups of -COF is the absorption frequency of 1883 cm due to -CF2COF. -1 The number of functional groups determined from the absorption peak of -CH2COF and the absorption frequency of 1840 cm -1 The number of functional groups is the sum of the number of functional groups determined from the absorption peaks of the compounds.
[0043] The number of -CF2H groups was measured using a nuclear magnetic resonance spectrometer at a temperature of (polymer melting point + 20)°C. 19 It can also be determined from the peak integral value of the -CF2H group by F-NMR measurement.
[0044] Functional groups such as -CF2H groups are functional groups present at the main chain terminal or side chain terminal of the fluorine-containing copolymer, and functional groups present in the main chain or side chain. These functional groups are introduced into the fluorine-containing copolymer, for example, by a chain transfer agent or polymerization initiator used in producing the fluorine-containing copolymer. For example, when an alcohol is used as a chain transfer agent or a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced into the main chain terminal of the fluorine-containing copolymer. Furthermore, the functional group is introduced into the side chain terminal of the fluorine-containing copolymer by polymerizing a monomer having a functional group.
[0045] A fluorocopolymer having the number of functional groups within the above range can be obtained by subjecting a fluorocopolymer having such functional groups to a wet heat treatment, a fluorination treatment, etc. The fluorocopolymer of the present disclosure is more preferably one that has been subjected to a wet heat treatment.
[0046] The melting point of the fluorine-containing copolymer is preferably 220 to 290° C., more preferably 240 to 280° C. When the melting point is within the above range, a more beautiful injection-molded article can be obtained by injection molding, a thin film of uniform thickness can be molded at a higher molding speed by extrusion molding, and a molded article having better abrasion resistance at 65° C., solvent crack resistance, low hydrogen permeability, rigidity at a high temperature of 75° C., tensile creep resistance at 130° C., and durability against repeated load can be obtained.
[0047] In this disclosure, melting points can be measured using a differential scanning calorimeter (DSC).
[0048] The hydrogen permeability coefficient of the fluorine-containing copolymer is preferably 1800 cm 3 mm / (m 224h atm) or less, and more preferably 1750cm 3 mm / (m 2 The fluorocopolymer of the present disclosure has an excellent low hydrogen permeability because the contents of HFP units and PPVE units and the melt flow rate are appropriately adjusted.
[0049] In the present disclosure, the hydrogen permeability coefficient can be measured under the conditions of a test temperature of 60° C. and a test humidity of 0% RH. The hydrogen permeability coefficient can be specifically measured by the method described in the examples.
[0050] The fluorine-containing copolymer of the present disclosure can be produced by any polymerization method such as bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. In these polymerization methods, the conditions such as temperature and pressure, polymerization initiator, chain transfer agent, solvent and other additives can be appropriately set depending on the composition and amount of the desired fluorine-containing copolymer.
[0051] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical initiator can be used.
[0052] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, for example: dialkyl peroxycarbonates such as di-normal propyl peroxydicarbonate, diisopropyl peroxydicarbonate, and di-sec-butyl peroxydicarbonate; Peroxyesters such as t-butyl peroxyisobutyrate and t-butyl peroxypivalate; Dialkyl peroxides such as di-t-butyl peroxide; Di[fluoro(or fluorochloro)acyl]peroxides; are some of the most representative examples.
[0053] Di[fluoro(or fluorochloro)acyl]peroxides include diacyl peroxides represented by [(RfCOO)-]2 (Rf is a perfluoroalkyl group, an ω-hydroperfluoroalkyl group, or a fluorochloroalkyl group).
[0054] Examples of di[fluoro(or fluorochloro)acyl]peroxides include di(ω-hydro-dodecafluorohexanoyl)peroxide, di(ω-hydro-tetradecafluoroheptanoyl)peroxide, di(ω-hydro-hexadecafluorononanoyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluoroparyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-decafluorohexanoyl)peroxide, Examples of the peroxide include di(ω-chlorotetradecafluorooctanoyl) peroxide, ω-hydrodecafluoroheptanoyl-ω-hydrohexadecafluorononanoyl peroxide, ω-chlorohexafluorobutylyl-ω-chlorodecafluorohexanoyl peroxide, ω-hydrododecafluoroheptanoyl-perfluorobutylyl peroxide, di(dichloropentafluorobutanoyl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecafluorooctanoyl) peroxide, di(pentachlorotetradecafluorodecanoyl) peroxide, and di(undecachlorotriacontafluorodocosanoyl) peroxide.
[0055] The water-soluble radical polymerization initiator may be a known water-soluble peroxide, such as ammonium salts, potassium salts, or sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, or percarbonate, t-butyl permaleate, or t-butyl hydroperoxide. A reducing agent such as a sulfite may also be contained, and the amount used may be 0.1 to 20 times the amount of the peroxide.
[0056] The use of an oil-soluble radical polymerization initiator as the polymerization initiator is preferred because it can avoid the generation of -COF and -COOH and easily adjust the total number of -COF and -COOH in the fluorine-containing copolymer to the above-mentioned range. Furthermore, the use of an oil-soluble radical polymerization initiator also tends to facilitate the adjustment of the carbonyl group-containing terminal group and -CHOH to the above-mentioned range. It is particularly suitable to produce the fluorine-containing copolymer by suspension polymerization using an oil-soluble radical polymerization initiator. The oil-soluble radical polymerization initiator is preferably at least one selected from the group consisting of dialkyl peroxycarbonates and di[fluoro(or fluorochloro)acyl]peroxides, and more preferably at least one selected from the group consisting of di-normal propyl peroxydicarbonate, diisopropyl peroxydicarbonate, and di(ω-hydro-dodecafluoroheptanoyl)peroxide.
[0057] Examples of chain transfer agents include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol, ethanol, and 2,2,2-trifluoroethanol; mercaptans such as methyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, chloroform, methylene chloride, and methyl chloride; and 3-fluorobenzotrifluoride. The amount added varies depending on the chain transfer constant of the compound used, but is usually used in the range of 0.01 to 20 parts by mass per 100 parts by mass of the solvent.
[0058] For example, when dialkyl peroxycarbonates, di[fluoro(or fluorochloro)acyl]peroxides, etc. are used as the polymerization initiator, the molecular weight of the resulting fluorine-containing copolymer becomes too high, and it may not be easy to adjust the melt flow rate to a desired level, but the molecular weight can be adjusted using a chain transfer agent. In particular, it is preferable to produce the fluorine-containing copolymer by suspension polymerization using a chain transfer agent such as an alcohol and an oil-soluble radical polymerization initiator.
[0059] Examples of the solvent include water, a mixed solvent of water and alcohol, etc. Furthermore, the monomer used in the polymerization of the fluorine-containing copolymer of the present disclosure can also be used as the solvent.
[0060] In suspension polymerization, a fluorine-based solvent may be used in addition to water. Examples of the fluorine-based solvent include hydrochlorofluoroalkanes such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, and CF2ClCF2CFHCl; chlorofluoroalkanes such as CF2ClCFClCF2CF3 and CF3CFClCFClCF3; and perfluoroalkanes such as perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, and CF3CF2CF2CF2CF2CF3. Of these, perfluoroalkanes are preferred. From the standpoints of suspension properties and economy, the amount of the fluorine-based solvent used is preferably 10 to 100 parts by mass per 100 parts by mass of the solvent.
[0061] The polymerization temperature is not particularly limited and may be 0 to 100° C. Furthermore, when a dialkyl peroxycarbonate, di[fluoro (or fluorochloro) acyl] peroxide, or the like is used as the polymerization initiator, and the decomposition rate of the polymerization initiator is too fast, it is preferable to adopt a relatively low polymerization temperature, such as a polymerization temperature in the range of 0 to 35° C.
[0062] The polymerization pressure is determined appropriately depending on other polymerization conditions such as the type and amount of solvent used, vapor pressure, and polymerization temperature, but may usually be 0 to 9.8 MPaG. The polymerization pressure is preferably 0.1 to 5 MPaG, more preferably 0.5 to 2 MPaG, and even more preferably 0.5 to 1.5 MPaG. Furthermore, when the polymerization pressure is 1.5 MPaG or higher, production efficiency can be improved.
[0063] Examples of additives used in polymerization include suspension stabilizers. The suspension stabilizer is not particularly limited as long as it is a conventionally known one, and examples include methyl cellulose and polyvinyl alcohol. The use of a suspension stabilizer stably disperses the suspended particles produced by the polymerization reaction in the aqueous medium, making it difficult for suspended particles to adhere to the reaction vessel, even when a stainless steel reactor without a glass lining or other anti-adhesion treatment is used. This allows the use of a reactor that can withstand high pressure, making polymerization possible under high pressure and improving production efficiency. In contrast, when polymerization is performed without the use of a suspension stabilizer, if a stainless steel reactor without an anti-adhesion treatment is used, suspended particles may adhere, resulting in a decrease in production efficiency. The concentration of the suspension stabilizer relative to the aqueous medium can be adjusted appropriately depending on the conditions.
[0064] When an aqueous dispersion containing a fluoropolymer is obtained by the polymerization reaction, the fluorocopolymer contained in the aqueous dispersion may be coagulated, washed, and dried to recover the dry fluoropolymer. When the fluorocopolymer is obtained as a slurry by the polymerization reaction, the slurry may be removed from the reaction vessel, washed, and dried to recover the dry fluoropolymer. By drying, the fluorocopolymer can be recovered in the form of a powder.
[0065] The fluorocopolymer obtained by polymerization may be formed into pellets. The method for forming the pellets is not particularly limited, and conventionally known methods can be used. For example, the fluorocopolymer may be melt-extruded using a single-screw extruder, twin-screw extruder, or tandem extruder, cut to a predetermined length, and formed into pellets. The extrusion temperature during melt extrusion must be varied depending on the melt viscosity of the fluorocopolymer and the production method, and is preferably from the melting point of the fluorocopolymer + 20°C to the melting point of the fluorocopolymer + 140°C. The method for cutting the fluorocopolymer is not particularly limited, and conventionally known methods such as strand cutting, hot cutting, underwater cutting, and sheet cutting can be used. The obtained pellets may be heated to remove volatile components therein (degassing treatment). The obtained pellets may be treated by contacting them with hot water at 30 to 200°C, steam at 100 to 200°C, or hot air at 40 to 200°C.
[0066] The fluorocopolymer obtained by polymerization may be heated to a temperature of 100°C or higher in the presence of air and water (wet heat treatment). Examples of wet heat treatment methods include using an extruder to melt and extrude the fluorocopolymer obtained by polymerization while supplying air and water. By wet heat treatment, thermally unstable functional groups such as -COF and -COOH in the fluorocopolymer can be converted to relatively thermally stable -CF2H, and the total number of -COF and -COOH groups, as well as the total number of carbonyl-containing terminal groups and -CH2OH groups in the fluorocopolymer, can be easily adjusted to within the above-mentioned ranges. Heating the fluorocopolymer in the presence of an alkali metal salt in addition to air and water can promote the conversion reaction to -CF2H. However, it should be noted that contamination by alkali metal salts should be avoided depending on the application of the fluorocopolymer.
[0067] The fluorine-containing copolymer obtained by polymerization may or may not be fluorinated. From the viewpoint of avoiding time and economic burdens, it is preferable not to fluorinate the fluorine-containing copolymer. The fluorination treatment can be carried out by contacting the unfluorinated fluorine-containing copolymer with a fluorine-containing compound. The fluorination treatment can convert the carbonyl group-containing terminal groups, thermally unstable functional groups such as -CHOH, and relatively thermally stable functional groups such as -CFH of the fluorine-containing copolymer to the extremely thermally stable -CF. As a result, the total number of carbonyl group-containing terminal groups and -CHOH of the fluorine-containing copolymer can be easily adjusted to the above-mentioned range.
[0068] The fluorine-containing compound is not particularly limited, but may be a fluorine radical source that generates fluorine radicals under fluorination treatment conditions, such as F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, or halogen fluorides (e.g., IF5, ClF3).
[0069] A fluorine radical source such as F2 gas may be 100% concentrated, but from a safety standpoint, it is preferably mixed with an inert gas and diluted to 5 to 50 mass %, more preferably 15 to 30 mass % for use. Examples of the inert gas include nitrogen gas, helium gas, and argon gas, with nitrogen gas being preferred from an economical standpoint.
[0070] The conditions for the fluorination treatment are not particularly limited, and the fluorine-containing copolymer in a molten state may be contacted with a fluorine-containing compound, but the treatment is usually carried out at a temperature below the melting point of the fluorine-containing copolymer, preferably 20 to 220°C, more preferably 100 to 200°C. The fluorination treatment is generally carried out for 1 to 30 hours, preferably 5 to 25 hours. The fluorination treatment is preferably carried out by contacting an unfluorinated fluorine-containing copolymer with fluorine gas (F2 gas).
[0071] A composition may be obtained by mixing the fluorine-containing copolymer of the present disclosure with other components as needed, such as fillers, plasticizers, processing aids, release agents, pigments, flame retardants, lubricants, light stabilizers, weather stabilizers, conductive agents, antistatic agents, UV absorbers, antioxidants, foaming agents, fragrances, oils, softeners, and dehydrofluorination agents.
[0072] Examples of fillers include silica, kaolin, clay, organoclay, talc, mica, alumina, calcium carbonate, calcium terephthalate, titanium oxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, and glass fibers. Examples of conductive agents include carbon black. Examples of plasticizers include dioctyl phthalate and pentaerythritol. Examples of processing aids include carnauba wax, sulfone compounds, low-molecular-weight polyethylene, and fluorine-based aids. Examples of dehydrofluorination agents include organic oniums and amidines.
[0073] Furthermore, as the other component, a polymer other than the above-mentioned fluorine-containing copolymer may be used. Examples of the other polymer include a fluororesin other than the above-mentioned fluorine-containing copolymer, a fluororubber, and a non-fluorinated polymer.
[0074] Examples of methods for producing the composition include a method of dry mixing the fluorocopolymer and other components, and a method of previously mixing the fluorocopolymer and other components in a mixer and then melt-kneading the mixture in a kneader, melt extruder or the like.
[0075] The fluorine-containing copolymer of the present disclosure or the above-mentioned composition can be used as a processing aid, molding material, etc., but is preferably used as a molding material. Aqueous dispersions, solutions, suspensions, and copolymer / solvent systems of the fluorine-containing copolymer of the present disclosure can also be used, and these can be applied as coatings or used for encapsulation, impregnation, and film casting. However, since the fluorine-containing copolymer of the present disclosure has the above-mentioned properties, it is preferably used as the above-mentioned molding material.
[0076] The fluorocopolymer of the present disclosure or the above-mentioned composition may be molded to obtain a molded article.
[0077] The method for molding the fluorine-containing copolymer or the composition is not particularly limited, and examples thereof include injection molding, extrusion, compression molding, blow molding, transfer molding, roto-molding, and roto-lining molding. Among these, the molding method is preferably extrusion, compression molding, injection molding, or transfer molding, and since molded articles can be produced with high productivity, injection molding, extrusion, or transfer molding is more preferred, and injection molding is even more preferred. That is, the molded article is preferably an extrusion-molded article, compression-molded article, injection-molded article, or transfer-molded article, and since they can be produced with high productivity, injection-molded article, extrusion-molded article, or transfer-molded article is more preferred, and injection-molded article is even more preferred. By molding the fluorine-containing copolymer of the present disclosure by injection molding, a beautiful molded article can be obtained.
[0078] Examples of molded articles containing the fluorinated copolymer of the present disclosure include nuts, bolts, joints, films, bottles, gaskets, wire coatings, tubes, hoses, pipes, valves, sheets, seals, packing, tanks, rollers, containers, cocks, connectors, filter housings, filter cages, flow meters, pumps, wafer carriers, and wafer boxes.
[0079] The fluorocopolymer of the present disclosure, the above composition, or the above molded article can be used, for example, in the following applications. Food packaging films, lining materials for fluid transfer lines used in food manufacturing processes, packings, sealing materials, sheets and other fluid transfer components for food manufacturing equipment; Chemical stoppers, packaging films, lining materials for fluid transfer lines used in pharmaceutical manufacturing processes, packings, sealing materials, sheets and other chemical transfer components; Inner lining materials for chemical tanks and pipes in chemical plants and semiconductor factories; O-rings, tubes, packings, valve core materials, hoses, seals, etc. used in automobile fuel systems and peripheral devices, as well as fuel transfer components such as hoses and seals used in automobile automatic transmission systems; Carburetor flange gaskets, shaft seals, valve stem seals, sealing materials, hoses, etc. used in automobile engines and peripheral devices, automobile brake hoses, air conditioner hoses, radiator hoses, electrical wire coating materials, and other automobile parts; Semiconductor manufacturing equipment O-rings, tubes, packing, valve core materials, hoses, seal materials, rolls, gaskets, diaphragms, joints and other chemical liquid transfer components for semiconductor devices; Paint rolls for painting equipment, hoses, tubes, ink containers and other paint and ink components; Food and beverage tubes and food and beverage hoses and other tubes, hoses, belts, packings, joints and other food and beverage transport components, food packaging materials, glass cooking equipment; Waste liquid transport components such as tubes and hoses for transporting waste liquid; High-temperature liquid transport components such as tubes and hoses for transporting high-temperature liquids; Steam piping components such as steam piping tubes and hoses; Anti-corrosion tapes for piping, such as tapes wrapped around piping on ship decks, etc.; Various coating materials such as electrical wire coating materials, optical fiber coating materials, transparent surface coating materials and backing materials to be applied to the light incident surface of photovoltaic elements in solar cells; Sliding parts such as diaphragms for diaphragm pumps and various packings; Agricultural films, weather-resistant covers for various roofing materials and side walls; Interior materials used in the construction industry, and glass covering materials such as non-flammable fire-resistant safety glass; Lining materials such as laminated steel sheets used in the home appliance sector;
[0080] Further examples of the fuel transfer members used in the fuel systems of the above-mentioned automobiles include fuel hoses, filler hoses, evaporation hoses, etc. The above-mentioned fuel transfer members can also be used as fuel transfer members for sour gasoline, alcohol-resistant fuels, and fuels containing gasoline additives such as methyl tertiary butyl ether-resistant and amine-resistant.
[0081] The chemical stoppers and packaging films for chemicals have excellent chemical resistance to acids, etc. Another example of the chemical liquid transfer member is anticorrosion tape that is wrapped around pipes in chemical plants.
[0082] Examples of the molded article include automobile radiator tanks, chemical tanks, bellows, spacers, rollers, gasoline tanks, containers for transporting waste liquids, containers for transporting high-temperature liquids, and tanks for fishing and fish farming.
[0083] Further examples of the molded article include components used for automobile bumpers, door trims, instrument panels, food processing equipment, cooking appliances, water- and oil-repellent glass, lighting-related equipment, display panels and housings for office automation equipment, illuminated signs, displays, liquid crystal displays, mobile phones, printed circuit boards, electric and electronic components, miscellaneous goods, trash cans, bathtubs, modular baths, ventilation fans, lighting frames, etc.
[0084] A molded article containing the fluorocopolymer of the present disclosure has excellent abrasion resistance at 65°C, solvent crack resistance, low hydrogen permeability, rigidity at a high temperature of 75°C, tensile creep resistance at 130°C, and durability against repeated loads, and can therefore be suitably used for housings for storing filters or adsorbents, piping members, tubes, films, wire coatings, etc.
[0085] A molded article containing the fluorocopolymer of the present disclosure can be suitably used as a compressed member such as a gasket, packing, etc. The compressed member of the present disclosure may be a gasket or packing.
[0086] The size and shape of the compressible member of the present disclosure may be appropriately set depending on the application and are not particularly limited. The shape of the compressible member of the present disclosure may be, for example, annular. Furthermore, the compressible member of the present disclosure may have a shape such as a circle, an oval, or a rectangle with rounded corners in a plan view, and may have a through hole in the center.
[0087] The compressed member of the present disclosure is preferably used as a member for constituting a nonaqueous electrolyte battery. The compressed member of the present disclosure is particularly suitable as a member used in a state in contact with the nonaqueous electrolyte in the nonaqueous electrolyte battery. That is, the compressed member of the present disclosure may have a surface in contact with the nonaqueous electrolyte in the nonaqueous electrolyte battery.
[0088] The nonaqueous electrolyte battery is not particularly limited as long as it is a battery containing a nonaqueous electrolyte, and examples thereof include a lithium ion secondary battery, a lithium ion capacitor, etc. Furthermore, examples of components constituting the nonaqueous electrolyte battery include a sealing member, an insulating member, etc.
[0089] The nonaqueous electrolyte may be one or more of known solvents, such as, but not limited to, propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyl lactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. The nonaqueous electrolyte battery may further include an electrolyte. The electrolyte may be, but is not limited to, LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, or the like.
[0090] The compressible member of the present disclosure can be suitably used, for example, as a sealing member such as a sealing gasket or sealing packing, or an insulating member such as an insulating gasket or insulating packing. A sealing member is a member used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. An insulating member is a member used for electrical insulation. The compressible member of the present disclosure may be a member used for both sealing and insulating purposes.
[0091] The compressible member of the present disclosure can be suitably used as a sealing member for a nonaqueous electrolyte battery or an insulating member for a nonaqueous electrolyte battery. Furthermore, since the compressible member of the present disclosure contains the above-mentioned fluorine-containing copolymer, it has excellent insulating properties. Therefore, when the compressible member of the present disclosure is used as an insulating member, it firmly adheres to two or more conductive members, preventing short circuits for a long period of time.
[0092] The fluorine-containing copolymer of the present disclosure can be suitably used as a material for forming an electric wire coating. A coated electric wire having a coating layer containing the fluorine-containing copolymer of the present disclosure exhibits excellent electrical properties since there is almost no variation in the outer diameter.
[0093] The coated electric wire comprises a core wire and a coating layer surrounding the core wire and containing the fluorinated copolymer of the present disclosure. For example, the coating layer can be an extrusion molded product obtained by melt-extrusion molding the fluorinated copolymer of the present disclosure onto the core wire. The coated electric wire is suitable for LAN cables (Ethernet Cables), high-frequency transmission cables, flat cables, heat-resistant cables, etc., and is particularly suitable for transmission cables such as LAN cables (Ethernet Cables) and high-frequency transmission cables.
[0094] The core wire may be made of a metal conductor material such as copper or aluminum. The core wire preferably has a diameter of 0.02 to 3 mm. The core wire diameter is more preferably 0.04 mm or more, even more preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. The core wire diameter is more preferably 2 mm or less.
[0095] Specific examples of the core wire include AWG (American Wire Gauge)-46 (solid copper wire with a diameter of 40 micrometers), AWG-26 (solid copper wire with a diameter of 404 micrometers), AWG-24 (solid copper wire with a diameter of 510 micrometers), and AWG-22 (solid copper wire with a diameter of 635 micrometers).
[0096] The thickness of the coating layer is preferably 0.1 to 3.0 mm, and more preferably 2.0 mm or less.
[0097] An example of a high-frequency transmission cable is a coaxial cable. A coaxial cable generally has a structure in which an inner conductor, an insulating coating layer, an outer conductor layer, and a protective coating layer are laminated in this order from the core to the outer periphery. A molded article containing the fluorine-containing copolymer of the present disclosure can be suitably used as an insulating coating layer containing a fluorine-containing copolymer. The thickness of each layer in the above structure is not particularly limited, but typically the inner conductor has a diameter of about 0.1 to 3 mm, the insulating coating layer has a thickness of about 0.3 to 3 mm, the outer conductor layer has a thickness of about 0.5 to 10 mm, and the protective coating layer has a thickness of about 0.5 to 2 mm.
[0098] The coating layer may contain bubbles, and it is preferable that the bubbles are uniformly distributed in the coating layer.
[0099] The average bubble diameter of the bubbles is not limited, but is preferably 60 μm or less, more preferably 45 μm or less, even more preferably 35 μm or less, even more preferably 30 μm or less, particularly preferably 25 μm or less, and especially preferably 23 μm or less. The average bubble diameter is preferably 0.1 μm or more, more preferably 1 μm or more. The average bubble diameter can be determined by taking an electron microscope image of the cross section of the wire, calculating the diameter of each bubble through image processing, and averaging the results.
[0100] The coating layer may have an expansion rate of 20% or more, more preferably 30% or more, even more preferably 33% or more, and even more preferably 35% or more. There is no particular upper limit, but it is, for example, 80%. The upper limit of the expansion rate may be 60%. The expansion rate is a value calculated by ((specific gravity of wire coating material - specific gravity of coating layer) / specific gravity of wire coating material) × 100. The expansion rate can be adjusted appropriately depending on the application, for example, by adjusting the amount of gas introduced into the extruder described below, or by selecting the type of gas to be dissolved.
[0101] The covered electric wire may have another layer between the core wire and the covering layer, or may have another layer (outer layer) around the covering layer. When the covering layer contains bubbles, the electric wire of the present disclosure may have a two-layer structure (skin-foam) in which a non-foamed layer is inserted between the core wire and the covering layer, a two-layer structure (foam-skin) in which a non-foamed layer is covered on the outer layer, or even a three-layer structure (skin-foam-skin) in which a non-foamed layer is covered on a skin-foam outer layer. The non-foamed layer is not particularly limited and may be a resin layer made of a resin such as a TFE / HFP copolymer, a TFE / PAVE copolymer, a TFE / ethylene copolymer, a vinylidene fluoride polymer, a polyolefin resin such as polyethylene (PE), or polyvinyl chloride (PVC).
[0102] The coated electric wire can be produced, for example, by heating the fluorine-containing copolymer using an extruder and extruding the fluorine-containing copolymer in a molten state onto a core wire to form a coating layer.
[0103] When forming the coating layer, the fluorocopolymer is heated and, in a molten state, a gas is introduced into the fluorocopolymer, thereby forming the coating layer containing bubbles. Examples of the gas that can be used include chlorodifluoromethane, nitrogen, carbon dioxide, and other gases, or mixtures of the above gases. The gas may be introduced into the heated fluorocopolymer as a pressurized gas, or may be generated by mixing a chemical foaming agent into the fluorocopolymer. The gas dissolves in the molten fluorocopolymer.
[0104] Furthermore, the fluorine-containing copolymer of the present disclosure can be suitably used as a material for high-frequency signal transmission products.
[0105] The high-frequency signal transmission product is not particularly limited as long as it is a product used for transmitting high-frequency signals, and examples include (1) molded plates such as insulating plates for high-frequency circuits, insulators for connecting parts, and printed wiring boards, (2) molded articles such as bases for high-frequency vacuum tubes and antenna covers, and (3) coated electric wires such as coaxial cables and LAN cables. The high-frequency signal transmission product can be suitably used in devices that use microwaves, particularly microwaves of 3 to 30 GHz, such as satellite communication devices and mobile phone base stations.
[0106] In the above-mentioned high-frequency signal transmission product, the fluorine-containing copolymer of the present disclosure can be suitably used as an insulator because of its low dielectric loss tangent.
[0107] The (1) molded plate is preferably a printed wiring board because it can provide good electrical properties. Examples of the printed wiring board include, but are not limited to, printed wiring boards for electronic circuits in mobile phones, various computers, communication devices, etc. The (2) molded article is preferably an antenna cover because it has low dielectric loss.
[0108] The fluorine-containing copolymer of the present disclosure can be suitably used for films.
[0109] The film of the present disclosure is useful as a release film. The release film can be produced by molding the fluorocopolymer of the present disclosure by melt extrusion molding, calendar molding, press molding, casting molding, etc. From the viewpoint of obtaining a uniform thin film, the release film can be produced by melt extrusion molding.
[0110] The film of the present disclosure can be applied to the surface of a roll used in office automation equipment. The fluorocopolymer of the present disclosure can be molded into a required shape by extrusion molding, compression molding, press molding, or the like to form a sheet, film, or tube, and used as a surface material for office automation equipment rolls, office automation equipment belts, etc. In particular, thin-walled tubes and films can be produced by melt extrusion molding.
[0111] The fluorine-containing copolymer of the present disclosure can also be suitably used for tubes, bottles, and the like.
[0112] Although the embodiments have been described above, it will be understood that various changes in form and details can be made without departing from the spirit and scope of the claims. [Example]
[0113] Next, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.
[0114] The values in the examples were measured by the following methods.
[0115] (Monomer unit content) The content of each monomer unit in the fluorine-containing copolymer was measured using an NMR analyzer (for example, AVANCE300 high temperature probe manufactured by Bruker Biospin) or an infrared absorption analyzer (Spectrum One manufactured by PerkinElmer).
[0116] (Melt flow rate (MFR)) The MFR of the fluorocopolymer was determined in accordance with ASTM D-1238 by measuring the mass (g / 10 min) of the polymer flowing out of a die having an inner diameter of 2 mm and a length of 8 mm at 372°C under a load of 5 kg per 10 min using a Melt Indexer G-01 (manufactured by Toyo Seiki Seisakusho, Ltd.).
[0117] (Number of -CF2H) The number of -CF2H groups in the fluorine-containing copolymer was measured using a nuclear magnetic resonance spectrometer AVANCE-300 (manufactured by Bruker Biospin) at a measurement temperature of (melting point of polymer + 20)°C. 19 F-NMR measurement was performed, and the peak integral value of the -CF2H group was used to determine the valence.
[0118] (Number of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2) The dried powders or pellets obtained in the examples and comparative examples were molded by cold pressing to produce films with thicknesses of 0.25 to 0.3 mm. The films were scanned 40 times using a Fourier transform infrared spectrometer (FT-IR (Spectrum One, manufactured by PerkinElmer)) to obtain infrared absorption spectra. The obtained infrared absorption spectra were compared with those of known films to determine the type of end group. Furthermore, the absorption peaks of specific functional groups appearing in the difference spectrum between the obtained infrared absorption spectrum and that of known films were used to determine the number of carbon atoms in the sample (1 × 10) according to the following formula (A): 6 The number of functional groups per molecule, N, was calculated.
[0119] N=I×K / t (A) I: Absorbance K: Correction coefficient t: film thickness (mm)
[0120] For reference, the absorption frequencies, molar absorption coefficients, and correction coefficients for the functional groups in the examples are shown in Table 2. The molar absorption coefficients were determined from FT-IR measurement data of low molecular weight model compounds.
[0121] [Table 2]
[0122] (Number of -OC(=O)OR (carbonate groups)) Analysis was performed using the method described in International Publication No. 2019 / 220850. The absorption frequency was 1817 cm -1The number of -OC(=O)OR (carbonate groups) was calculated in the same manner as for calculating the number of functional groups N, except that the molar absorbance coefficient was set to 170 (l / cm / mol) and the correction factor was set to 1426.
[0123] (Melting Point) The melting point of the fluorocopolymer was determined using a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science Corporation) by first heating from 200°C to 350°C at a heating rate of 10°C / min, subsequently cooling from 350°C to 200°C at a cooling rate of 10°C / min, and then heating a second time from 200°C to 350°C at a heating rate of 10°C / min, and then determining the melting point from the peak of the melting curve occurring during the second heating process.
[0124] Comparative Example 1 40.25 kg of deionized water and 0.191 kg of methanol were added to a 174 L autoclave equipped with a stirrer, and the autoclave was thoroughly evacuated and replaced with nitrogen. The autoclave was then evacuated, and 40.25 kg of HFP and 0.52 kg of PPVE were added to the evacuated autoclave. The autoclave was then heated to 30.0 °C. TFE was then added until the internal pressure of the autoclave reached 0.914 MPa. Then, 0.63 kg of an 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to initiate polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.914 MPa, and the set pressure was maintained by continuously adding TFE. 1.5 hours after the start of polymerization, an additional 0.191 kg of methanol was added. Two and four hours after the start of polymerization, an additional 0.63 kg of DHP was added to reduce the internal pressure by 0.001 MPa, and six hours later, 0.48 kg was added to reduce the internal pressure by 0.001 MPa. After that, an additional 0.13 kg of DHP was added every two hours until the reaction was completed, reducing the internal pressure by 0.001 MPa each time.
[0125] PPVE was added in 0.15 kg increments when the continuously added amount of TFE reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. Furthermore, when the added amount of TFE reached 6.0 kg and 18.1 kg, 0.191 kg of methanol was added to the autoclave. The polymerization was terminated when the added amount of TFE reached 40.25 kg. After the polymerization was completed, the unreacted TFE and HFP were released to obtain a wet powder. This wet powder was then washed with pure water and dried at 150 °C for 10 hours to obtain 46.2 kg of dry powder.
[0126] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Ikegai Co., Ltd.) to obtain pellets of the copolymer. Various physical properties of the obtained pellets were measured using the methods described above. The results are shown in Table 3.
[0127] Comparative Example 2 Copolymer pellets were obtained in the same manner as in Comparative Example 1, except that the amount of methanol added before the start of polymerization was changed to 0.319 kg, the amounts of methanol added in installments after the start of polymerization were each changed to 0.319 kg, the amount of PPVE added before the start of polymerization was changed to 0.35 kg, the amount of PPVE added in installments after the start of polymerization was changed to 0.10 kg, and the pressure set inside the autoclave before and after the start of polymerization was changed to 0.921 MPa. Various physical properties were measured using the obtained pellets using the methods described above. The results are shown in Table 3.
[0128] Comparative Example 3 40.25 kg of deionized water and 0.349 kg of methanol were added to a 174 L autoclave equipped with a stirrer, and the autoclave was thoroughly evacuated and replaced with nitrogen. The autoclave was then evacuated, and 40.25 kg of HFP and 0.40 kg of PPVE were added to the evacuated autoclave. The autoclave was then heated to 25.5 °C. TFE was then added until the internal pressure of the autoclave reached 0.843 MPa. Then, 1.25 kg of an 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to initiate polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.843 MPa, and the set pressure was maintained by continuously adding TFE. 1.5 hours after the start of polymerization, an additional 0.349 kg of methanol was added. Two and four hours after the start of polymerization, 1.25 kg of DHP was added to reduce the internal pressure by 0.002 MPa, and 6 hours later, 0.96 kg was added to reduce the internal pressure by 0.002 MPa. After that, 0.25 kg of DHP was added every two hours until the reaction was completed, reducing the internal pressure by 0.002 MPa each time.
[0129] PPVE was added in 0.10 kg increments when the continuously added amount of TFE reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. Furthermore, when the added amount of TFE reached 6.0 kg and 18.1 kg, 0.349 kg of methanol was added to the autoclave. The polymerization was terminated when the added amount of TFE reached 40.25 kg. After the polymerization was completed, the unreacted TFE and HFP were released to obtain a wet powder. This wet powder was then washed with pure water and dried at 150 °C for 10 hours to obtain 45.1 kg of dry powder.
[0130] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Ikegai Co., Ltd.) to obtain pellets of the copolymer. Various physical properties of the obtained pellets were measured using the methods described above. The results are shown in Table 3.
[0131] Comparative Example 4 Copolymer pellets were obtained in the same manner as in Comparative Example 1, except that the amount of methanol added before the start of polymerization was changed to 0.169 kg, the amounts of methanol added in installments after the start of polymerization were each changed to 0.169 kg, the amount of PPVE added before the start of polymerization was changed to 0.55 kg, the amount of PPVE added in installments after the start of polymerization was changed to 0.15 g, and the pressure set inside the autoclave before and after the start of polymerization was changed to 0.923 MPa. Various physical properties were measured using the obtained pellets using the methods described above. The results are shown in Table 3.
[0132] Comparative Example 5 Copolymer pellets were obtained in the same manner as in Comparative Example 1, except that the amount of methanol charged before the start of polymerization was changed to 0.357 kg, the amounts of methanol charged in installments after the start of polymerization were changed to 0.357 kg each, the addition of PPVE before and after the start of polymerization was eliminated, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.928 MPa. Various physical properties were measured using the obtained pellets by the methods described above. The results are shown in Table 3.
[0133] Comparative Example 6 Copolymer pellets were obtained in the same manner as in Comparative Example 1, except that the amount of methanol added before the start of polymerization was changed to 0.229 kg, the amount of methanol added in installments after the start of polymerization was changed to 0.229 kg each, the amount of PPVE added before the start of polymerization was changed to 0.80 kg, the amount of PPVE added in installments after the start of polymerization was changed to 0.22 g each, and the pressure set inside the autoclave before and after the start of polymerization was changed to 0.928 MPa. The HFP content and PPVE content were measured using the obtained pellets by the methods described above. The results are shown in Table 3.
[0134] The resulting pellets were degassed in an electric furnace at 200°C for 8 hours and then placed in a vacuum vibration reactor VVD-30 (Okawahara Manufacturing Co., Ltd.) and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced until atmospheric pressure was reached. 0.5 hours after the introduction of F2 gas, the reactor was evacuated once and F2 gas was introduced again. 0.5 hours later, the reactor was evacuated again and F2 gas was introduced again. Subsequently, the above F2 gas introduction and evacuation operations were repeated once per hour, and the reaction was carried out at 200°C for 8 hours. After the reaction was completed, the atmosphere inside the reactor was thoroughly replaced with N2 gas to terminate the fluorination reaction and obtain pellets. Various physical properties of the resulting pellets were measured using the methods described above. The results are shown in Table 3.
[0135] Comparative Example 7 945 g of deionized water and 6.1 g of methanol were placed in a 4 L autoclave equipped with a stirrer, and the autoclave was thoroughly evacuated and replaced with nitrogen. The autoclave was then evacuated, and 945 g of HFP and 12.9 g of PEVE were placed in the evacuated autoclave. The autoclave was then heated to 30.0 °C. TFE was then added until the internal pressure of the autoclave reached 0.926 MPa. Then, 14.7 g of an 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to initiate polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.926 MPa, and the set pressure was maintained by continuously adding TFE. 1.5 hours after the start of polymerization, an additional 6.1 g of methanol was added. Two and four hours after the start of polymerization, an additional 14.7 g of DHP was added and the internal pressure was reduced by 0.001 MPa, and six hours later, 11.3 g was added and the internal pressure was reduced by 0.001 MPa. After that, an additional 3.0 g of DHP was added every two hours until the reaction was completed, and the internal pressure was reduced by 0.001 MPa each time.
[0136] PEVE was added in 3.7 g increments when the continuously added amount of TFE reached 190 g and 380 g, respectively. Furthermore, when the added amount of TFE reached 140 g, 6.1 g of methanol was added to the autoclave. Polymerization was terminated when the added amount of TFE reached 454 g. After polymerization was completed, unreacted TFE and HFP were released to obtain a wet powder. This wet powder was then washed with pure water and dried at 150 °C for 10 hours to obtain 519 g of dry powder.
[0137] The resulting powder was melt-extruded at 370°C using a 14φ screw extruder (manufactured by Imoto Machinery Co., Ltd.) to obtain copolymer pellets. The HFP content and PEVE content of the resulting pellets were measured using the methods described above. The results are shown in Table 3.
[0138] The resulting pellets were degassed in an electric furnace at 200°C for 8 hours and then placed in a portable reactor TVS1 (manufactured by Taiatsu Glass Kogyo Co., Ltd.) and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced until atmospheric pressure was reached. 0.5 hours after the introduction of F2 gas, the reactor was evacuated once and F2 gas was introduced again. 0.5 hours later, the reactor was evacuated again and F2 gas was introduced again. Thereafter, the above F2 gas introduction and evacuation operations were repeated once per hour, and the reaction was carried out at 200°C for 8 hours. After the reaction was completed, the atmosphere inside the reactor was thoroughly replaced with N2 gas to terminate the fluorination reaction and obtain pellets. The resulting pellets were used to measure various physical properties using the methods described above. The results are shown in Table 3.
[0139] Example 1 Copolymer pellets were obtained in the same manner as in Comparative Example 1, except that the amount of methanol added before the start of polymerization was changed to 0.294 kg, the amounts of methanol added in installments after the start of polymerization were each changed to 0.294 kg, the amount of PPVE added before the start of polymerization was changed to 0.33 kg, the amount of PPVE added in installments after the start of polymerization was changed to 0.09 g, and the pressure set inside the autoclave before and after the start of polymerization was changed to 0.937 MPa. Various physical properties were measured using the obtained pellets using the methods described above. The results are shown in Table 3.
[0140] Example 2 Copolymer pellets were obtained in the same manner as in Comparative Example 1, except that the amount of methanol added before the start of polymerization was changed to 0.296 kg, the amounts of methanol added in installments after the start of polymerization were each changed to 0.296 kg, the amount of PPVE added before the start of polymerization was changed to 0.45 kg, the amount of PPVE added in installments after the start of polymerization was changed to 0.12 g, and the pressure set inside the autoclave before and after the start of polymerization was changed to 0.933 MPa. Various physical properties were measured using the obtained pellets using the methods described above. The results are shown in Table 3.
[0141] Example 3 Copolymer pellets were obtained in the same manner as in Comparative Example 1, except that the amount of methanol added before the start of polymerization was changed to 0.305 kg, the amounts of methanol added in installments after the start of polymerization were changed to 0.305 kg each, the amount of PPVE added before the start of polymerization was changed to 0.48 kg, the amount of PPVE added in installments after the start of polymerization was changed to 0.13 g each, and the pressure set inside the autoclave before and after the start of polymerization was changed to 0.928 MPa. Various physical properties were measured using the obtained pellets using the methods described above. The results are shown in Table 3.
[0142] Example 4 Copolymer pellets were obtained in the same manner as in Comparative Example 1, except that the amount of methanol added before the start of polymerization was changed to 0.280 kg, the amounts of methanol added in installments after the start of polymerization were changed to 0.280 kg each, the amount of PPVE added before the start of polymerization was changed to 0.55 kg, the amount of PPVE added in installments after the start of polymerization was changed to 0.15 g each, and the pressure set inside the autoclave before and after the start of polymerization was changed to 0.923 MPa. The HFP content and PPVE content were measured using the obtained pellets by the methods described above. The results are shown in Table 3.
[0143] The obtained pellets were fluorinated in the same manner as in Comparative Example 6. The obtained pellets were used to measure various physical properties by the methods described above. The results are shown in Table 3.
[0144] [Table 3]
[0145] In Table 3, "Other (pieces / C10 6 The notation "<9" in Table 3 means that the number (total number) of -CF═CF groups is less than 9. The notation "<6" in Table 3 means that the number (total number) of the target functional group is less than 6. The notation "ND" in Table 3 means that no quantifiable peak was observed for the target functional group.
[0146] The pellets thus obtained were then evaluated for the following properties, the results of which are shown in Table 4.
[0147] (wear test) Using pellets and a heat press, sheet-like test specimens approximately 0.2 mm thick were prepared, and 10 cm x 10 cm test specimens were cut from these. The prepared test specimens were fixed to the test table of a Taber abrasion tester (No. 101 Special Taber Abrasion Tester, manufactured by Yasuda Seiki Seisakusho Co., Ltd.). Abrasion tests were performed using the Taber abrasion tester under the following conditions: test specimen surface temperature 65°C, load 500 g, abrasion wheel CS-10 (ground 20 times with #240 abrasive paper), and rotation speed 60 rpm. The test specimen was weighed after 1000 rotations, and then again after another 5500 rotations using the same test specimen. The abrasion loss was calculated using the following equation: Wear amount (mg)=M1-M2 M1: Test piece weight after 1000 rotations (mg) M2: Test piece weight (mg) after 5500 rotations
[0148] (Chemical immersion crack test) Approximately 50 g of the pellets were placed in a mold (inner diameter 120 mm, height 38 mm) and heated at 360 °C for 20 minutes using a hot plate press. The molded product was then water-cooled under 1 MPa pressure to produce a molded product with a thickness of approximately 2 mm. Three test specimens were obtained by punching the resulting sheet using a 13.5 mm x 38 mm rectangular dumbbell. A notch was made in the center of each long edge of each test specimen using a 19 mm x 0.45 mm blade in accordance with ASTM D1693. Three notched test specimens and 25 g of concentrated sulfuric acid were placed in a 100 mL polypropylene bottle and heated in an electric furnace at 95 °C for 20 hours. The notched test specimens were then removed. The three notched test specimens were mounted in a stress crack test fixture conforming to ASTM D1693 and heated in an electric furnace at 120 °C for 24 hours. The notches and their surrounding areas were visually inspected and the number of cracks was counted. A crack-free sheet has excellent solvent crack resistance. ○: The number of cracks is 0 ×: The number of cracks is one or more
[0149] (hydrogen permeability coefficient) Using the pellets and a heat press molding machine, sheet-like test pieces with a thickness of approximately 0.1 mm were prepared. The hydrogen permeability of the obtained test pieces was measured using a differential pressure gas permeability meter (L100-5000 gas permeability meter, manufactured by Systech Illinois) according to the method described in JIS K7126-1:2006. Permeation area: 50.24 cm 2 The hydrogen permeability was measured at a test temperature of 60°C and a test humidity of 0%RH. The hydrogen permeability coefficient was calculated using the obtained hydrogen permeability and the thickness of the test piece according to the following formula. Hydrogen permeability coefficient (cm 3 mm / (m 2 ·24h·atm))=GTR×d GTR: Hydrogen permeability (cm 3 / (m 2 24h ATM d: Test piece thickness (mm)
[0150] (75℃ load deflection rate) Using pellets and a heat press molding machine, sheet-like test pieces approximately 2.4 mm thick were prepared. 80 x 10 mm test pieces were cut from these and heated in an electric furnace at 100°C for 20 hours. Testing was performed using a heat distortion tester (manufactured by Yasuda Seiki Seisakusho Co., Ltd.) in accordance with the method described in JIS KK 7191-1, except that the test pieces obtained were used. Testing was performed using the flatwise method at a test temperature of 30 to 150°C, a heating rate of 120°C / hour, a bending stress of 1.8 MPa, and a test temperature of 30 to 150°C. The deflection under load was calculated using the following formula. Sheets with a small deflection under load at 75°C have excellent rigidity at high temperatures of 75°C. Load deflection rate (%) = a2 / a1 x 100 a1: thickness of test piece before test (mm) a2: Deflection at 75℃ (mm)
[0151] (Tensile creep test) Tensile creep strain was measured using a Hitachi High-Tech Science TMA-7100. A sheet approximately 0.1 mm thick was prepared using pellets and a heat press molding machine, and a sample 2 mm wide and 22 mm long was prepared from the sheet. The sample was attached to a measuring jig with a jig distance of 10 mm. A cross-sectional load of 3.71 N / mm was applied to the sample. 2 A load was applied so that the sample would not stretch, and the sample was left at 130°C. The sample's length displacement (mm) was measured from 90 minutes after the start of the test to 600 minutes after the start of the test, and the ratio of the length displacement (mm) to the initial sample length (10 mm) (tensile creep strain (%)) was calculated. Sheets with a small tensile creep strain (%) measured at 130°C for 600 minutes are less likely to stretch even when a tensile load is applied for a long period of time in a high-temperature environment, and have excellent high-temperature tensile creep resistance (130°C).
[0152] (tensile strength after 60,000 cycles) Tensile strength was measured after 60,000 cycles using a Shimadzu MMT-250NV-10 fatigue testing machine. A sheet approximately 2.4 mm thick was produced using pellets and a heat press molding machine. A dumbbell-shaped sample (2.4 mm thick, 5.0 mm wide, 22 mm long) was then prepared using an ASTM D1708 microdumbbell. The sample was attached to a measuring jig, which was then placed in a thermostatic chamber at 110°C. Uniaxial tension was repeated with a stroke of 0.2 mm and a frequency of 100 Hz, and the tensile strength (tensile strength at a stroke of +0.2 mm, unit: N) was measured for each tension.
[0153] The sheet maintains high tensile strength even after being subjected to 60,000 cycles, demonstrating excellent durability (at 110°C) against repeated loads.
[0154] (Injection moldability) Using an injection molding machine (SE50EV-A, manufactured by Sumitomo Heavy Industries, Ltd.), the fluorine-containing copolymer was injection molded at a cylinder temperature of 385°C, a mold temperature of 200°C, and an injection speed of 100 mm / s. The mold used was a Cr-plated HPM38 mold (15 mm x 15 mm x 1 mm, 4-cavity, side gate). The four injection-molded articles obtained were observed and evaluated according to the following criteria. The presence or absence of surface roughness was confirmed by touching the surface of the injection-molded article. 3: The entire surface of the four compacts is smooth. 2: Of the four molded bodies, one had surface roughness within 1 cm of the mold gate. 1: Of the four molded bodies, 2 to 4 had surface roughness within 1 cm of the mold gate. 0: Roughness was observed on the entire surface of all four compacts.
[0155] (Film formability) The pellets were extruded into a film using a φ14 mm extruder (manufactured by Imoto Manufacturing Co., Ltd.) and a T-die under the following extrusion conditions: a) Winding speed: 1m / min b) Roll temperature: 120℃ c) Film width: 70mm d) Thickness: 0.10mm e) Extrusion conditions: Single-screw extruder with a cylinder diameter of 14 mm and L / D of 20 Extruder temperature settings: Barrel C-1 (330°C), Barrel C-2 (350°C), Barrel C-3 (365°C), T-die (370°C)
[0156] The extrusion molding of the fluorocopolymer was continued until the fluorocopolymer could be stably extruded from the molding machine. Subsequently, the fluorocopolymer was extruded to produce a film 11 m or longer (70 mm wide) with a thickness of 0.10 mm. A 10-11 m portion was cut from the end of the obtained film to produce a test piece (1 m long, 70 mm wide) for measuring thickness variation. The thickness was measured at a total of three points: the center point in the width direction of the end of the produced film and two points 25 mm apart in the width direction from the center point. Furthermore, the thickness was measured at a total of nine points: three center points spaced 25 cm apart from the center point in the width direction of the end of the film toward the other end, and two points 25 mm apart in the width direction from each center point. A score of 0.01 was given if the number of measured values outside the range of ±10% of 0.10 mm out of a total of 12 measured values was 1 or less, and a score of 0.01 was given if the number of measured values outside the range of ±10% of 0.10 mm was 2 or more.
[0157] (Wire coating test) Using a 30 mm diameter electric wire coating molding machine (manufactured by Tanabe Plastic Machinery Co., Ltd.), 19 stranded silver-plated conductors, each 0.08 mm in diameter, were extrusion coated with a fluorine-containing copolymer to the following coating thickness to obtain a coated electric wire. The electric wire coating extrusion molding conditions were as follows. a) Core conductor: Conductor diameter approximately 0.40 mm (0.08 mm x 19 strands) b) Coating thickness: 0.30 mm c) Insulated wire diameter: 1.00 mm d) Wire withdrawal speed: 120 m / min e) Extrusion conditions: Single-screw extruder with a cylinder diameter of 30 mm and L / D of 24 Die (inner diameter) / Chip (outer diameter) = 10.0 mm / 4.0 mm Extruder temperature settings: Barrel C-1 (330°C), Barrel C-2 (360°C), Barrel C-3 (365°C), Head H (370°C), Die D-1 (370°C), Die D-2 (370°C). Core wire preheating was set to 80°C.
[0158] (Outer diameter variation) The outer diameter of the obtained coated electric wire was measured continuously for one hour using an outer diameter measuring instrument (ODAC18XY manufactured by Zumbach). The outer diameter fluctuation value was determined by rounding off the third decimal place of the outer diameter value that deviated most from the predetermined outer diameter value (1.00 mm). The ratio of the absolute value of the difference between the predetermined outer diameter and the outer diameter fluctuation value to the predetermined outer diameter (1.00 mm) (outer diameter fluctuation rate) was calculated and evaluated according to the following criteria. (Outer diameter fluctuation rate (%)) = |(Outer diameter fluctuation value) - (Specified outer diameter)| / (Specified outer diameter) × 100 ±1%: The outer diameter fluctuation rate is 1% or less ±2%: The fluctuation rate of the outer diameter is more than 1% and less than 2%. ×: The fluctuation rate of the outer diameter is more than 2%
[0159] (tube formability) The pellets were extruded using a φ30 mm extruder (manufactured by Tanabe Plastics Machinery Co., Ltd.) to obtain a tube with an outer diameter of 10.0 mm and a wall thickness of 1.0 mm under the following extrusion molding conditions. a) Die inner diameter: 25 mm b) Mandrel outer diameter: 13 mm c) Sizing die inner diameter: 10.5 mm d) Take-up speed: 0.4 m / min e)Outer diameter: 10.0mm f) Wall thickness: 1.0mm g) Extrusion conditions: Single-screw extruder with a cylinder diameter of 30 mm and L / D of 22 mm Extruder temperature settings: Barrel section C-1 (350°C), Barrel section C-2 (370°C), Barrel section C-3 (380°C), Head section H-1 (390°C), Die section D-1 (390°C), Die section D-2 (390°C) The obtained tube was observed and evaluated according to the following criteria: The appearance of the tube was confirmed visually. 〇: Appearance is good ×: The cross section is not circular, but is flat or has uneven thickness, and the appearance is poor.
[0160] [Table 4]
Claims
1. A fluorine-containing copolymer containing tetrafluoroethylene units, hexafluoropropylene units, perfluoro(propyl vinyl ether) units and other monomer units, The content of hexafluoropropylene units is 9.4 to 10.3 mass% based on the total monomer units, The content of perfluoro(propyl vinyl ether) units is 0.8 to 1.2 mass% based on the total monomer units; The content of other monomer units is 0 to 1.7% by mass based on the total monomer units; the content of tetrafluoroethylene units is selected so that the total content of hexafluoropropylene units, perfluoro(ethyl vinyl ether) units, tetrafluoroethylene units and other monomer units is 100% by mass; The melt flow rate at 372°C is 7.0 to 17.0 g / 10 min. Fluorine-containing copolymer.
2. 2. The fluorine-containing copolymer according to claim 1, wherein the content of the hexafluoropropylene unit is 9.6 to 10.2 mass % based on the total monomer units.
3. 3. The fluorine-containing copolymer according to claim 1, wherein the content of the perfluoro(propyl vinyl ether) unit is 0.8 to 1.1 mass % based on the total monomer units.
4. 4. The fluorine-containing copolymer according to claim 1, which has a melt flow rate at 372° C. of 7.5 to 15.0 g / 10 min.
5. -CF 2 The number of H is 10 main chain carbon atoms. 6 5. The fluorine-containing copolymer according to claim 1, wherein the number of the fluorine-containing units per unit area is 50 or more.
6. Carbonyl-containing end groups, -CF=CF 2 and -CH 2 The total number of OH groups is 10 6 6. The fluorine-containing copolymer according to claim 1, wherein the number of fluorine-containing units per unit area is 90 or less.
7. An injection molded article comprising the fluorine-containing copolymer according to any one of claims 1 to 6.
8. A coated electric wire having a coating layer containing the fluorine-containing copolymer according to any one of claims 1 to 6.
9. A molded article comprising the fluorocopolymer according to any one of claims 1 to 6, which is a housing for storing a filter or an adsorbent, a piping member, a tube, a film or a wire covering.